Respuesta :

we are given

[tex]sin^{-1}(tan(\frac{\pi}{4}))[/tex]

Let's assume entire term as x

[tex]sin^{-1}(tan(\frac{\pi}{4}))=x[/tex]

now, we can take both sides as sin

[tex]sin(sin^{-1}(tan(\frac{\pi}{4})))=sin(x)[/tex]

since, sin and sin^-1 are inverse of each other

so, they will get cancelled

and we get

[tex]tan(\frac{\pi}{4})=sin(x)[/tex]

now, we know that

tan(pi/4)=1

[tex]1=sin(x)[/tex]

and sin is 1 at pi/2

so, we get

[tex]x=\frac{\pi}{2}[/tex]

so, option-D.........Answer

Answer:

D

Step-by-step explanation:

ACCESS MORE